The Greenhouse effect and coastal area of Bangladesh : proceedings of an international conference held in Dhaka, Bangladesh, 5th March, 1989 - Moudud, Hasna Jasimuddin; Coastal Area Resource Development and Management Association (Bangladesh); International Seminar on the Greenhouse Effect and the Coastal Area of Bangladesh Dhaka, Bangladesh) (Dhaka, Bangladesh : Coastal Area Resource Development and Management Association, 1989)
Papers presented at the International Seminar on the Greenhouse Effect and the Coastal Area of Bangladesh organized by the Coastal Area Resource Development and Management Association, Bangladesh.
Includes bibliographical references.
IMRAN
Keywords: Greenhouse, Atmospheric -- Bangladesh -- Congresses; Coasts -- Environmental aspects -- Bangladesh -- Congresses